Apremio personal por falta de pagos en alimentos en el código orgánico de la niñez y adolescencia no contempla en las personas con discapacidad severa o enfermedades catastróficas - Jiménez Ponce, Washington Boanergers (2016)
Our Constitution in article 11 paragraph 2 of the Constitution of the Ecuador says that "all persons are equal and enjoy the same rights, duties and opportunities. No one may be discriminated against on grounds of ethnic group, place of birth, age, sex, gender identity, cultural identity, marital status, language, religion, ideology, political affiliation, judicial history, socio-economic condition, immigration status, sexual orientation, State of health, carry HIV, disability, physical differences; or by any other distinction, Personal or collective, temporary or permanent, have as their object or result impairing or nullifying the recognition, enjoyment or exercise of the rights. The law shall punish all forms of discrimination. The State shall take affirmative action measures that promote real equality in favour of holders of rights who are in a situation of inequality. It is to say that the Constitution grants equal rights and obligations for all citizens, so that they can demand and exercise their rights. Likewise, article 35 of the Constitution of the Republic of Ecuador, expressed; Older adults, girls, children and adolescents, pregnant women, persons with disabilities, persons deprived of liberty and those who suffer catastrophic diseases or high complexity, will receive priority and specialized in the fields of public and private care. The same priority will receive persons in situation of risk, victims of domestic and sexual violence, child abuse, natural disasters or anthropogenic. The State will provide special protection to persons in double vulnerability. In this regard, it can be said that the Constitution of the Republic of Ecuador, guarantees the rights of so-called vulnerable people, in such a way that are considered in this case priority persons with disabilities, granting them as such care, warranty and in some cases exceptions. Our current legal regulations, determines in the organic code of childhood and adolescence, in relation to the right of food that it must comply with the obligation to cancel pension food the child, taking into account always the economic capacity of the recipient and the needs of the recipient. The rights of children in terms of food are of a very personal nature may be demanded at any time, are rights that the State guarantees from the Constitution, such as the right to food which is dialectically evolving within need them basic and existential children, therefore the State through all of its institutions should ensure the enforcement of laws and ensure the effectiveness of the rights guaranteed in the Constitution and international rights. Now, besides this also the same legal body, likewise States that who does not comply with this obligation and under request of a party may ask for a liquidation of assets due and if this were in arrears for a period of two months, may apply to the judge that will turn a ballot of personal urgency for the recipient. In this Regulation no exception of persons which our legislation establishes with severe disabilities and also people who suffer from catastrophic illnesses, it considered that those who suffer from these disabilities or diseases must have priority, differential or preferential treatment of the vulnerable sector of society. Hence, the organic law on disabilities, "aims to ensure the prevention, early detection, habilitation and rehabilitation of disability and the full force, broadcasting and exercise of the rights of persons with disabilities, established in the Constitution of the Republic, treaties and international instruments; as well as, those who has laws related to gender, generational and intercultural". It is worth mentioning that it is State obligation to guarantee to persons with disabilities or suffering from catastrophic diseases the right to care in the public and private fields and part of that priority, and as such they must have certain exception in fulfillment of some obligations, in this case food, in order to be guaranteed and recognized in form expresses their rights and they are monitored.